2011
DOI: 10.1121/1.3365315
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic ship signature measurements by cross-correlation method

Abstract: Cross-correlation methods were applied for the estimation of the power spectral density and modulation spectrum of underwater noise generated by moving vessels. The cross-correlation of the signal from two hydrophones allows the separation of vessel acoustic signatures in a busy estuary. Experimental data recorded in the Hudson River are used for demonstration that cross-correlation method measured the same ship noise and ship noise modulation spectra as conventional methods. The cross-correlation method was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…We have addressed this shortcoming by developing a technique to separate the DEMON signatures using the cross-correlation of signals arriving at various hydrophones. The presented results are based on application of cross-correlation method for DEMON ship signature extraction [18,19]. These papers showed the applicability of the cross-correlation method for the separation of the ship acoustic signature in one simple example.…”
Section: Introductionmentioning
confidence: 89%
“…We have addressed this shortcoming by developing a technique to separate the DEMON signatures using the cross-correlation of signals arriving at various hydrophones. The presented results are based on application of cross-correlation method for DEMON ship signature extraction [18,19]. These papers showed the applicability of the cross-correlation method for the separation of the ship acoustic signature in one simple example.…”
Section: Introductionmentioning
confidence: 89%
“…Within the project framework, two autonomous acoustic detection units were deployed next to the promontory of Portofino, each one equipped with a hydrophone array which can record both the typical acoustic signal emitted by the dolphin (social communication whistle) (Zimmer, 2011) and the sound produced by boat engines (Fillinger et al, 2011). The detection units communicate via radio link with the ground station, located inside the Portofino lighthouse.…”
Section: Arion Projectmentioning
confidence: 99%
“…The boat tracking algorithm is based on the cross-correlation method (Fillinger et al, 2011) and on custom-made improvements made to it (Brunoldi et al, 2016). It obtains the direction of the acoustic source, through the cross-correlation signals of two different hydrophone pairs.…”
Section: Motor Boat Detection and Trackingmentioning
confidence: 99%
“…Those few studies carried out in confined coastal and inland waterways that are found in the literature have focused on a variety of issues, including acoustic scintillation to estimate current flow (Di Iorio and Farmer, 1994), active sonar systems for biological stock assessment and fisheries management (Xie, 2000), homeland security applications (Stolkin et al, 2006), acoustical communication (van Walree et al, 2007, acoustical monitoring of tidal bores (Zhu et al, 2010), marine mammal surveys (Dong et al, 2011), seasonal trends in a large remote fjord (McConnell et al, 1992), recreational boat noise in waterways (Haviland-Howell et al, 2007), ambient noise in freshwater habitats (Wysocki et al, 2007), high-frequency noise spectra in shallow brackish water (Poikonen, 2010), long-term noise trends in large, industrialized rivers (Vracar and Mijic, 2011), acoustical monitoring of ship traffic (Fillinger et al, 2011), acoustic attenuation properties in a river (Roh et al, 2008), sitespecific acoustic propagation models for the lower Hudson River Estuary (Radhakrishnan, 2009), and acoustic quantification of stratified turbulence in the Connecticut River (Lavery et al, 2013).…”
mentioning
confidence: 99%